2017
DOI: 10.1002/jcu.22563
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sonography and MRI in the evaluation of stability of capitellar osteochondritis dissecans

Abstract: PurposeTo compare the diagnostic accuracies of ultrasonography (US) and magnetic resonance imaging (MRI) with intraoperative capitellar osteochondritis dissecans (COCD) fragment stability findings.MethodsPatients whose International Cartilage Repair Society (ICRS) osteochondritis dissecans (OCD) classifications were I/II (stable) or III (unstable) were included. Patients underwent preoperative US and MRI. On US, lesions were evaluated as unstable when irregular contours of the chondral surface were observed. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…The corresponding rate between each finding determined from the MCFI and those determined intraoperatively were evaluated. We calculated the corresponding rate as follows: (number of cases in which the findings determined by the MCFI corresponded to the actual intraoperative findings)/(total number of cases) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding rate between each finding determined from the MCFI and those determined intraoperatively were evaluated. We calculated the corresponding rate as follows: (number of cases in which the findings determined by the MCFI corresponded to the actual intraoperative findings)/(total number of cases) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The subchondral bone and articular cartilage of the humeral capitellum are affected, and several possible causes, including repetitive microtrauma and genetic factors, are implicated [ 3 , 4 , 6 , 7 ]. Although the stability and size of the lesion are considered important factors impacting lesion severity [ 6 , 8 , 9 , 10 ], no single imaging modality can adequately predict lesion severity [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], thereby presenting a challenge to elbow surgeons. A recent study by Pu et al concluded that a combination of radiography, computed tomography (CT), and magnetic resonance imaging (MRI) can most accurately determine OCD lesion stability by compensating for the respective flaws of the individual modalities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, ultrasound achieved superior results than MRI. 42 Further studies on the use of ultrasound diagnostic are needed to confirm these findings in a larger group of patients.…”
Section: Diagnosticsmentioning
confidence: 96%
“…Wie bereits beschrieben tritt Als Diagnostikum zur Evaluation der Fragmentstabilität hat die Sonographie an Aufmerksamkeit ebenfalls gewonnen. Die Unterscheidung zwischen instabilen und stabilen Fragmenten zeigt sich hierbei durch eine chondrale Konturunterbrechung, wie bereits in mehreren Studien belegt werden konnte [31,57].…”
Section: Einleitung Definition Und äTiologieunclassified